Electrochemical splitting of water on IrO2 based Nafion bonded composite anode for efficient production of low cost and clean hydrogen fuel - Sonkar S.; Pramanik H. (My University, 2025)
Hydrogen gas of ultrapure form has been produced via electrochemical splitting of water molecules using an efficient water electrolysis method. The IrO2 based low-cost composite anode has been developed in the laboratory to split water molecules via electrolysis with the cathode electrocatalyst as Pt (40 % by wt.)/CHSA. The electrocatalysts loading at anode and cathode are 1 mg/cm2 at both electrodes. Other components of the manufactured electrodes are Nafion® (5 wt%) ionomer dispersion, PTFE, and isopropyl alcohol. The electrolyzer is fabricated using a perspex sheet i.e., polymethyl methacrylate. The rate of hydrogen production is measured for different applied currents, voltage, and concentrations of H2SO4 electrolyte in the electrolysis mode at a temperature of 20 ℃. The IrO2 composites anode used as oxygen evolution reaction are studied by electrochemical impedance studies (EIS) and cyclic voltammetry to evaluate the electrocatalytic activity and charge transfer resistance of the developed composite anode. The IrO2 anode electrode exhibits a higher HER activity concentration of 0.75 M H2SO4 electrolyte than that of the 0.25 M and 0.50 M H2SO4 electrolyte concentration as is shown by EIS. The highest hydrogen production rate of 0.9 mL/min is obtained at the voltage of 1.9 V and applied current of 0.1 A using the electrolyte concentration of 0.75 M H2SO4. However, the hydrogen production rate is very low (0.33 mL/min.) when a low voltage of 1.6 V and current of 0.04 A was applied at the same concentration of electrolyte (0.75 M) H2SO4. IrO2 is known to be one of the most active electrocatalysts for the oxygen evolution reaction in a liquid electrolyte, exhibiting high electronic conductivity and stability in the electrochemical system. © 2024, National Institute of Science Communication and Policy Research. All rights reserved.